2012
DOI: 10.1146/annurev-polisci-031710-100955
|View full text |Cite
|
Sign up to set email alerts
|

How (and Why) Is This Time Different? The Politics of Economic Crisis in Western Europe and the United States

Abstract: This article compares government responses to the Great Recession of [2008][2009] with government responses to recessions and other economic challenges in the period 1974-1982. We focus on five countries: France, Germany, Sweden, the United Kingdom, and the United States. Across these countries, we observe two broad shifts in crisis responses. First, governments have in the recent period eschewed heterodox crisis policies and relied more exclusively on fiscal stimulus. Second, tax cuts have become a more impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(76 citation statements)
references
References 18 publications
2
73
0
1
Order By: Relevance
“…Chung & Thewissen, 2011;Lallement, 2011) and those who emphasize convergence (e.g. Pontusson & Raess, 2012;Shahidi, 2015) and pointing at the strengthening of neoliberal policy agendas across Europe (Hermann 2014). Our interview analysis showed how the Great Recessions triggered reactions in labour and social welfare policy which are highly path dependent, but sit within a broader framework of (neoliberal) convergence.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chung & Thewissen, 2011;Lallement, 2011) and those who emphasize convergence (e.g. Pontusson & Raess, 2012;Shahidi, 2015) and pointing at the strengthening of neoliberal policy agendas across Europe (Hermann 2014). Our interview analysis showed how the Great Recessions triggered reactions in labour and social welfare policy which are highly path dependent, but sit within a broader framework of (neoliberal) convergence.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…http://www.livewhat.unige.ch/ fundamental changes are the result of path dependencies shaping policymaking (Chung & Thewissen, 2011;Kersbergen et al, 2014;Lallement 2011;Pontusson & Raess, 2012. Apart from the fact that large-scale organizations and redistributive institutional arrangements are difficult and costly to reform, there are also ideational components that create path dependent pressures.…”
Section: Path Dependency Convergence and The European Welfare State mentioning
confidence: 99%
See 2 more Smart Citations
“…The corporatism-4 pluralism debate also highlighted that institutions shaped crisis responses during the 1970s in the aftermath of the oil shocks (Crouch, 1983;Lehmbruch and Schmitter, 1982;Molina and Rhodes, 2002 More generally, much of the political economy literature suggests that institutional differences can cause constrasting reactions to common shocks or common trends, such as the rise of the service economy (Iversen and Wren, 1998;Iversen and Soskice, 2015) or globalisation (Garrett 1998). On the other hand, while recent scholarship has shown that differences between liberal and coordinated market economies may have contributed to the build-up of global imbalances and the global economic crisis (Iversen and Soskice, 2012), there is no strong evidence to suggest that such differences have systematically shaped the variation in crisis responses across the OECD (Pontusson and Raess, 2012).…”
Section: Institutions Crises and Economic Policymentioning
confidence: 99%